PRIORITY TO SECURED CREDITORS IN THE REGIME OF SARFAESI ACT, RDB ACT AND IBC (International Journal of Food and Nutritional Sciences, 2022)
Creation of assets is the basis of lending and such charged assets form part of ‘security interest’ created in favour of the lenders for the purpose of enforcement. Section 35 of the Securitization and Reconstruction of Financial Assets and Enforcement of Security Interest Act, 2002 (SARFAESI Act) states that the provisions of the SARFAESI Act shall have overriding effect over other laws. Similarly, Section 34 of the Recovery of Debts and Bankruptcy Act, 1993 (RDB Act) states that the provisions of the RDB Act shall have overriding effect over other laws. Statutory First charge has been embedded by virtue of various legislations in order to secure the Government dues. There is no such corresponding provision in the SARFAESI Act, RDB Act or the Insolvency and Bankruptcy Code, 2016 (IBC) by which creation of first charge in favour of Banks or Secured Creditors qua the property of the Borrower is available. However, priority to Secured Creditor over Governmental dues are provided under Section 26E of the SARFAESI Act and Section 31B of RDB Act and also superior class of priority ranking has been conferred to Secured Creditor in distribution of sale proceeds of liquidation asset as per Section 53 of the IBC. This article is an attempt to deal with the provisions of law relating to priority to the secured creditors under the three enactments, viz, SARFAESI, RDB and IBC and to place the judicial pronouncements on the subject.